Biofilm inhibition in oral pathogens by nanodiamonds. (17th May 2021) - Zhang, Tongtong; Kalimuthu, Shanthini; Rajasekar, Vidhyashree; Xu, Feng; Yiu, Yau Chuen; Hui, Tony K. C.; Neelakantan, Prasanna; Chu, Zhiqin
Abstract : Nanodiamonds were demonstrated to have great effects on inhibiting biofilm formation as well as disrupting the preformed biofilm in several selected orally and systemically important organisms. Abstract : Complex microbial communities, e.g., biofilms residing in our oral cavity, have recognized clinical significance, as they are typically the main cause for infections. Particularly, they show high resistance to conventional antibiotics, and alternatives including nanotechnology are being intensively explored nowadays to provide more efficient therapeutics. Diamond nanoparticles, namely, nanodiamonds (NDs) with many promising physico-chemical properties, have been demonstrated to work as an effective antibacterial agent against planktonic cells (free-floating state). However, little is known about the behaviors of NDs against biofilms (sessile state). In this study, we uncovered their role in inhibiting biofilm formation and their disrupting effect on preformed biofilms in several selected orally and systemically important organisms. The current findings will advance the mechanistic understanding of NDs on oral pathogens and might accelerate corresponding clinical translation.